Mapping Current Trends in Electricity-Saving Behaviour: A Bibliometric Study - Quang Pham, Van; Vuong, Tuan Khanh (International Journal of Energy Economics and Policy, 2025)
This study explored 1,230 publications related to electricity-saving behaviour (ESB), extracted from the Web of Science database. Prior to 2010, research in this field was limited, with fewer than 20 publications per year. The results show that academic interest in the field has risen sharply since 2015, with a peak of over 160 publications in 2021. This growth reflects increasing concern over sustainable energy and climate change, as well as interest in influencing individual and household behaviours related to energy reduction. While the study of ESB is relatively young, it has developed quickly. Analysis of institutional contributions revealed the U.S. Department of Energy, the Beijing Institute of Technology and the University of California to be the top contributors, indicating their significant research accomplishments and a commitment to sustainability research. ESB is a globally important subject with contributions from a range of countries. China was the top contributor with nearly 370 publications, followed by England, Italy, India and Spain. VOSviewer was used to visualise keyword co-occurrence, revealing significant clusters around “behavior,” “energy efficiency” and “conservation.” The keyword analysis also revealed a significant shift from a focus on technological initiatives, such as “smart meters” and “buildings,” to an emphasis on the psychological and environmental components of “habit,” “climate” and “residents” in more recent studies. Together, the findings demonstrate the interdisciplinary nature and increasing complexity of ESB research and have significant implications for future research and policy in the field of energy conservation and sustainable development.